Doing Business 2014 : Understanding Regulations for Small and Medium-Size Enterprises. - Bank, World (Doing Business., 2013)
Eleventh in a series of annual reports comparing business regulation in 189 economies, Doing Business 2014 measures regulations affecting 11 areas of everyday business activity:Starting a businessDealing with construction permitsGetting electricityRegistering propertyGetting creditProtecting investorsPaying taxesTrading across bordersEnforcing contractsClosing a businessEmploying workersThe report updates all indicators as of June 1, 2013, ranks economies on their overall ""ease of doing business"", and analyzes reforms to business regulation - identifying which economies are strengthening the.